Factors that influenced purchase intention toward private label products among employees in Melaka International College of Science and Technology (MiCoST) / Zakirah Zaid - Zaid, Zakirah (Faculty of Business and Management, 2018)
This study is to determine the relationship between store image, perceived quality and familiarity towards purchase intention of private label products among employees of Melaka International College of Science and Technology (MiCoST). A quantitative approach and descriptive research design was used in this study. There three hypotheses were proposed to test the relationship between store image, perceived quality and familiarity with the purchase intention toward private label products. The research instrument was structured by questionnaires. All staff of MiCoST was been selected for this study. For this study, there were 120 of population and 92 workers have been selected for the sample. This study used simple random sampling technique to select the sample of this research. Besides that, multiple regression analysis, correlation and frequency were used to determine the relationship between store image, perceived quality, familiarity and purchase intention toward private label products. Based on this study, there is a significant relationship between store image and perceived quality with purchase intention toward private label products. The study also showed that there was no significant relationship between familiarity and the purchase intention toward private label products. All the results conducted by Statistical Package for the Social Science (SPSS) Software.